Participatory Learning and Action untuk Menumbuhkan Quality of Life pada Kelompok Keluarga Harapan - Darmawan, Dadan; Alamsyah, Trian Pamungkas; Rosmilawati, Ila (Journal of Nonformal Education and Community Empowerment, 2020)
Thos Study aims to answer the practices of Participatory Learning and Action (PLA) in the Keluarga Harapan Group in Serang City, Banten Province. Participatory Learning and Action (PLA) or Learning From acting in a participatory manner. Learning and acting together or participatory action -reflection. Participatory learning and action (PLA) is an approach to the learning process and interacting with the community or society. In fact, this approach combines various participatory methods to facilitate collectivity and learning processes in the community. Whereas the participatory Learning and action (PLA) approach is closely related to the community empowerment process where the Program Keluarga Harapan (PKH) is one of the community empowerment programs. This Study used a qualitative approach by exploring data from PKH facilitators and recipients. The results of the research show that this implementation process involves a lot of community participation as a Participatory Learning and Action (PLA) step where it is the main point of implementing needs-based empowerment programs. So that PLA becomes an encouragement fo PKH recipients to behave protively, have a good quality of life and be able to optimize insights in the use of education or health.